Concept Attainment Model for Enhancing Conceptual Understanding in Seventh-Grade Students at Junior High School - Firjon Nurisna Hadi Al Haq; Sikky El Walida; Fadhila Kartika Sari (Journal of Development Research, 2023)
This research aims to describe the implementation of the Concept Attainment Model in teaching conceptual understanding of quadrilaterals, specifically parallelograms and rectangles. The research subjects were 22 students from grade VII. This study was conducted through two cycles of classroom action research. Each cycle consisted of planning, acting, observing, and reflecting stages. Data collection techniques included observation, concept understanding tests, and interviews. The research results showed that the test scores in cycle 1 and cycle 2 were 67.8 and 78.68, with an increase of 10.88, and the average percentage of students who met the Minimum Mastery Criteria in Cycle 2 was 77.27%. The teacher's success rate in conducting activities in cycle 1 and cycle 2 was 59.54% and 79.54%, respectively, indicating a 20% improvement. Meanwhile, the percentage of students' activity observation results in cycle 1 and cycle 2 was 59.58% and 78.75%, respectively, showing a 19.78% improvement.